Determinant Cash Waqf Payment Amongst Rural Society in Yogyakarta: Do Itsar and Culture Matters? - Melis, Melis; Misnen Ardiansyah; Abdul Qoyum (Nurani, 2025)
Cash waqf, within the framework of sharia economic law, serves as a crucial instrument for enhancing social welfare. When managed effectively and in accordance with sharia principles, cash waqf can provide substantial benefits for society. As of 2022, Indonesia had a population of approximately 275.78 million, with 86.93% identifying as Muslims, thus has a huge potential for generating waqf funds. However, data from the Indonesian Waqf Board (BWI) indicate that the total cash waqf collection in 2021 amounted to IDR 831 billion, whereas the potential for cash waqf in 2022 to reach IDR 130 trillion. This considerable disparity motivated the present study to explore the factors influencing individuals' willingness to pay cash waqf. This study specifically examines the determinants affecting interest in cash waqf payment among rural communities in the Special Region of Yogyakarta. Employing the Structural Equation Model (SEM) analysis tool with SmartPLS, the study revealed that the variables Itsar (altruism) and gotong royong (mutual cooperation) has positive effect on individuals' willingness for cash waqf payment, as evidenced by their respective p-values of 0.000 (< 0.05). Whereas, three variables—knowledge, income, and education level—do not significantly influence individuals' interest in cash waqf payment. These results suggests that in rural areas, particularly in Yogyakarta, strong communal values such as solidarity and cooperative spirit play a pivotal role in fostering cash waqf payments.